Effects of different postharvest treatments on glucosinolate metabolism and nutritional quality in Brassica vegetables: A review - WANG Mengyu; YUAN Wenxin; MIAO Huiying; WANG Bingliang; WANG Qiaomei (浙江大学学报. 农业与生命科学版)
Brassica vegetables are rich in glucosinolates, a group of secondary metabolites, which is related to flavor, quality, resistance and anticancer activity. In addition, they also play a vital role in plant defense against pathogens and herbivores. In this review, we briefly elucidated the biosynthetic and degradation pathway of glucosinolate, and highlighted the effects of different postharvest treatments, such as cooling storage, controlled atmosphere storage, modified atmosphere packaging, 1-methylcyclopropene (1-MCP) treatment, as well as processing and cooking methods on compositions and contents of glucosinolate profiles and nutritional quality in Brassica vegetables. Particularly, from the perspective of dynamic equilibrium of glucosinolate metabolism, we analyzed the mechanism of regulating glucosinolate components and contents, and also discussed how to maintain the contents of favorable glucosinolate profiles and nutritional quality in Brassica vegetable products during postharvest period.